A multicentre randomised controlled trial of an intervention to improve the accuracy of linear growth measurement. Issue 4 (19th March 2004) - Lipman, T H; Hench, K D; Benyi, T; Delaune, J; Gilluly, K A; Johnson, L; Johnson, M G; McKnight-Menci, H; Shorkey, D; Shults, J; Waite, F L; Weber, C
Abstract : Aims: To evaluate linear growth assessment and the effect of an intervention on measurement accuracy in primary care practices (PCP) within eight US geographical areas. Methods: In this multicentre randomised controlled intervention study, paediatric endocrine nurses as site coordinators (SC) visited 55 randomly assigned PCP to evaluate growth assessment of staff performing linear measurements. SC observed 127 measurers assessing a total of 878 children: 307 (baseline), 282 (3 months), and 289 (6 months). Accuracy was determined by SC re-measuring each child with correct technique and equipment. State of the art equipment and a standardised growth training session were provided to the intervention group (IG) following the baseline visit. SC repeated data collection at all PCP at 3 and 6 months. Results: There were no baseline differences between IG and CG equipment, technique, or accuracy; only 30% of measurements were accurate (⩽0.5 cm from SC). Post-intervention, significantly more IG measurements were accurate: IG = 55%, CG = 37% at 3 months; IG = 70%, CG = 34% at 6 months. Odds ratio of accuracy for IG versus CG was 2.1 at 3 months and 4.5 at 6 months. At 6 months, mean difference from the SC measurements was 0.5 cm in IG and 1.1 cm in CG. Conclusions: In PCP, children are measured inaccurately. Our intervention significantly improved measurement accuracy. Improved accuracy could yield more rapid detection and diagnosis of paediatric growth disorders.